UPAYA MENINGKATKAN AKTIVITAS DAN PRESTASI BELAJAR MATEMATIKA SISWA MELALUI METODE PERMAINAN DI KELAS V SDN 004 BELANTARAYA - Rosman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article is classroom action research, which aims to increase students’ learning activity and achievement at SDN 004. The subjects in the research involved 26 students at SDN 004, which consist of 11 male and 15 female students. The method used in the research is descriptive quantitative, which explains or describes a factual problem based on phenomena that occurred in the research field. The results indicate that applying games can increase students’ learning activities and mathematics learning achievement. It is proven that the students’ average value before applying treatment is 52. After making learning improvements applied by the researcher in the first cycle of the first daily test, the average value of students’ mathematics learning outcomes of 76 students increased to 14.6% compared to the initial result before making learning improvements. In the second cycle of the second daily test, the average score of students' mathematics learning outcomes is 92 increased to 17.6% compared to the initial result before making learning improvements. Based on the learning outcomes data, students’ learning achievement has increased well after applying learning improvements in the form of applying games that could make students more active and creative in developing ideas and solving various learning topics.